The Impact of Globalization on the Development of Vietnam's Business Law - LAM, Nguyen Van (Revista Jurídica Portucalense, 2024)
Over the years, globalization has helped Vietnam's economy achieve significant achievements, and business activities are closely related to regional and international countries. Up to now, the legal system has recognized and created conditions for the implementation of the basic principles of the socialist-oriented market economy. However, legal regulations are still general, do not ensure synchronization, and consistency, and are not closely associated with integration requirements. The needs of practice pose a need to study and analyze the legal realities and propose to improve the process of developing and implementing business laws by the reality and the process of international economic integration. This article uses the method of systematization, synthesis, analysis, interpretation of the law and the method of legal comparison, etc. to assess, evaluate, and analyze theoretical and practical issues about the globalization process, and the impacts of globalization on the laws governing aspects of business activities, as well as to analyze new needs and solutions to promote the process of deep integration in the context of Vietnam's globalization.